The Diagnostic Role Of The Complement C3,C4 In Patients With Systemic Lupus Erythematosis - رضوان فيصل; أسعد رمال; القطاش علي (Latakia University Journal -Medical Sciences Series, 2021)
Systemic lupus erythemetosis (SLE) is an autoimmune disease and chronic systemic disease with unknown etiology influential more than one million individuals each year. The aim of this study is to substantiation the impact of C3,C4 in patients with Systemic lupus erythemetosis. During the period 2/January/2019 to 1/October/2020, thirty three patients (32femal: 1male) with Systemic lupus erythemetosis that diagnosed by specialist with ages ranged between (15-60) years, by using C3,C4 immunturbidimetric test. of all patient, 33% have low level of serum C3, 12% have low level of serum C4